Predicting regional accents of Bengali language using deep learning - Ibrahim, Md. Abu; Nayeem, Md. Nawaz-S-Salekeen; Al Arabi, Sadaf (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.